Corrigendum to “Quality-assurance of heat-flow data: the new structure and evaluation scheme of the IHFC Global Heat Flow Database” [Tectonophysics 863 (2023) / 229976] - Sven Fuchs; Ben Norden; Florian Neumann; Norbert Kaul; Akiko Tanaka; Ilmo T. Kukkonen; Christophe Pascal; Rodolfo Christiansen; Gianluca Gola; Jan Šafanda; Orlando Miguel Espinoza-Ojeda; Ignacio Marzan; et al. (Tectonophysics, 2026)

Mercury biomagnification and microbial adaptation in a mining-impacted Amazonian River - Maria Camila Escobar; Juan Pablo Niño-Garcia; Astrid Acosta; Marcela Núñez-Avellaneda; Edwin Agudelo Córdoba; Jhonatan Caicedo; Alejandro Acosta-Gonzalez; Yaneth Vasquez; José Luis Marrugo-Negrete; Silvia Marqués; Gladys Cardona (Journal of Hazardous Materials, 2025)

Biosurfactant production by Rhodococcus ALDO1 isolated from olive mill wastes - Paola Sanmartin Negrete; Carolina Ghilardi; Lina Rodriguez Pineda; Ethel Pérez; Maria Lidia Herrera; Virginia Borroni (Biocatalysis and Agricultural Biotechnology, 2024)

Microbial diversity and abundance of Hg related genes from water, sediment and soil the Colombian amazon ecosystems impacted by artisanal and small-scale gold mining - Gladys Inés Cardona; Maria Camila Escobar; Alejandro Acosta-González; Natalie Díaz-Ruíz; Juan Pablo Niño-García; Yaneth Vasquez; José Marrugo-Negrete; Silvia Marqués (Chemosphere, 2024)

Quality-assurance of heat-flow data: The new structure and evaluation scheme of the IHFC Global Heat Flow Database - Sven Fuchs; Ben Norden; Florian Neumann; Norbert Kaul; Akiko Tanaka; Ilmo T. Kukkonen; Christophe Pascal; Rodolfo Christiansen; Gianluca Gola; Jan Šafanda; Orlando Miguel Espinoza-Ojeda; Ignacio Marzan; et al. (Tectonophysics, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Ecological regime shift drives declining growth rates of sea turtles throughout the West Atlantic - Karen A. Bjorndal; Alan B. Bolten; Milani Chaloupka; Vincent S. Saba; Cláudio Bellini; Maria A. G. Marcovaldi; Armando J. B. Santos; Luis Felipe Wurdig Bortolon; Anne B. Meylan; Peter A. Meylan; Jennifer Gray; Robert Hardy; et al. (Global Change Biology, 2017)
Somatic growth is an integrated, individual‐based response to environmental conditions, especially in ectotherms. Growth dynamics of large, mobile animals are particularly useful as bio‐indicators of environmental change at regional scales. We assembled growth rate data from throughout the West Atlantic for green turtles, Chelonia mydas , which are long‐lived, highly migratory, primarily herbivorous mega‐consumers that may migrate over hundreds to thousands of kilometers. Our dataset, the largest ever compiled for sea turtles, has 9690 growth increments from 30 sites from Bermuda to Uruguay from 1973 to 2015. Using generalized additive mixed models, we evaluated covariates that could affect growth rates; body size, diet, and year have significant effects on growth. Growth increases in early years until 1999, then declines by 26% to 2015. The temporal (year) effect is of particular interest because two carnivorous species of sea turtles—hawksbills, Eretmochelys imbricata, and loggerheads, Caretta caretta —exhibited similar significant declines in growth rates starting in 1997 in the West Atlantic, based on previous studies. These synchronous declines in productivity among three sea turtle species across a trophic spectrum provide strong evidence that an ecological regime shift ( ERS ) in the Atlantic is driving growth dynamics. The ERS resulted from a synergy of the 1997/1998 El Niño Southern Oscillation ( ENSO )—the strongest on record—combined with an unprecedented warming rate over the last two to three decades. Further support is provided by the strong correlations between annualized mean growth rates of green turtles and both sea surface temperatures ( SST ) in the West Atlantic for years of declining growth rates ( r = −.94) and the Multivariate ENSO Index ( MEI ) for all years ( r = .74). Granger‐causality analysis also supports the latter finding. We discuss multiple stressors that could reinforce and prolong the effect of the ERS . This study demonstrates the importance of region‐wide collaborations.

Parkinsonism Signs and Symptoms in Agricultural Pesticide Handlers in Washington State - Susan Searles Nielsen; Shu-Ching Hu; Harvey Checkoway; Maria Negrete; Pablo Palmández; Theresa Bordianu; Brad A. Racette; Christopher D. Simpson (Journal of Agromedicine, 2017)